The social representation of Christian orthodox monasticism in contemporary Russia - Ksenia S. Medvedeva (Социологический журнал, 2015)
The article discusses the public opinion about Christian Orthodox monasteries and monasticism in contemporary Russia. The analysis is based on the results of the public opinion polls conducted in 2010–2015 by the Russian Public Opinion Research Center (VCIOM). Materials of the poll by Irina Aster (2009) and multimedia contest “Russia 10” (2013) were also used for the analysis. The analysis shows that monasteries are considered by Russians to be one of the symbols of the country although kept in a “passive cultural stock.” Educated and older respondents seem to be more familiar with famous historical monastics rather than less educated and young people. Public opinion paints the portrait of a hard-working “prayful” monk, whose life choice can be explained using divergent paradigms of “moving away” from the world and “coming to” a monastery, the latter connected with religious and moral issues. Respondents give a wide and varied range of positive motives in joining a monastery than negative ones. However, the attitude of Russians to the potential intention of their relative to become a monk is ambiguous. Polls show a roughly equal share of those whose reaction to such a decision would be “rather positive” or “rather negative.” It is concluded that the image of the monk as the “inok,” the religious “other” is quite acceptable in the modern social and cultural sphere. Monasticism is the cornerstone of Christianity, so the transformation of this institution, as well as the dynamics of public opinion about it can demonstrate the changes in the place and role of religion in society, which is especially relevant given the decline of trust in traditional institutions in contemporary social-cultural space.